Meningkatkan Pengetahuan dan Sikap Tentang Toksoplasmosis Pada Remaja Putri Pemelihara Kucing Melalui Program "SELAMAT" - Faisal, St. Rahmah Dianislamiati; Rifani, Rohmah (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The incidence of toxoplasmosis cases continues to increase with the prevalence of cases in Indonesia ranging between 43-88%. Humans can be infected through cat feces which contain Toxoplasma gondii oocysts, so cat keepers need good knowledge and attitudes about Toxoplasmosis, but currently, many cat keepers still don't know about Toxoplasmosis. Research related to Toxoplasmosis is also still very limited. The aim of the research was to determine the effectiveness of the "SELAMAT" program intervention to increase knowledge and attitudes about Toxoplasmosis among female cat keepers. The research used a quasi-experimental one group pre-posttest design method. Participants in the research were 12 young women who keep cats at SMAN 10 Makassar. This study used a Toxoplasmosis knowledge scale and a Toxoplasmosis attitude scale. The results of data analysis used the Wilcoxon signed-rank test with z values = -3.063 and -3.081 and Asymp. Sig = 0.002 (p < 0.05). This research shows an increase in knowledge with an average value of 2.42 increasing to 5.5 and attitudes with an average value of 22.67 increasing to 39.17. The results show that there has been a significant increase in knowledge and attitudes. It can be concluded that the "SELAMAT" program is effective in increasing knowledge and attitudes about Toxoplasmosis among female cat keepers. This research contributes to increasing understanding and awareness about Toxoplasmosis among female cat keepers in preventing transmission of Toxoplasmosis by implementing the HBM model.